Prevalence and Economic Impact of Bovine Fasciolosis at Kampala City Abattoir, Central Uganda - Joan, Nambafu; Stephen, Musisi John; Bashir, Mwambi; Kiguli, James; Orikiriza, Patrick; Bazira, Joel; Itabangi, Herbert; Stanley, Iramiot J. (British Microbiology Research Journal, 2015)
Aim: This study was carried out to determine the prevalence of bovine fasciolosis in indigenous cattle slaughtered in Kampala City abattoir and to compare the diagnostic efficiency of fecal and post mortem examination. The study also assessed the economic impact of bovine fasciolosis associated with liver condemnation in the abattoir and weight loss to the animal. Methods: A cross sectional, experimental study of bovine fasciolosis was conducted using postmortem liver and fecal examination of slaughtered animals. A total of 511 slaughtered cattle were examined at post mortem and Fasciola species were recorded. The number of eggs per gram of feces was determined using the standard McMaster method (14). The formulae a+b+cto determine the total annual loss was used according to Ogunrinade and Adegoke 1982. Results: Of the 511 livers and fecal samples examined, 429(84%) and 358(70%) were positive for fasciolosis respectively. The most common Fasciola species affecting the cattle was F. gigantica (73.3%), followed by F. hepatica (5.68%). Mixed infections and unidentified or immature forms of Fasciola spp. were present in 0.59%, and 4.31% of cattle, respectively. The prevalence of fasciolosis recorded in this study was higher than that reported by other researchers in Uganda. The study also showed a strong relationship between fecal examination and postmortem findings of liver lesions though postmortem examination may be considered a better diagnostic tool forfasciolosis (k=213, P<0.05). Theabattoir lost a total of 231,186,550,000 Uganda shillings (92,474,620 US Dollars) annually on totally condemned liver. Conclusion: The prevalence of bovine fasciolosis amongst cattle slaughtered in Kampala City Trader’s abattoir is high. Great economic losses as a result of condemnation of infected livers were incurred, and that F. gigantica is the main species of liver flukes affecting cattle in all districts of Uganda. Local climatic factors, cattle population and the presence of the snail intermediate hosts are probably the main drivers influencing the incidence of the disease in the various districts of the country. This disease therefore deserves serious attention by the various stakeholders in order to promote the beef industry in the study area in particular and in the country in general.
Keywords: Cattle; Economic impact; Fasciola gigantic; Fasciolosis; Fasciola hepatica; Prevalence.